'Unprepared for the depth of my feelings' - Capturing grief in older people through research poetry. (12th March 2022) - Gerber, Katrin; Brijnath, Bianca; Lock, Kayla; Bryant, Christina; Hills, Danny; Hjorth, Larissa
Abstract: Background: Older people are more likely to experience bereavements than any other age group. However, in healthcare and society, their grief experiences and support needs receive limited attention. Through innovative, arts-based research poetry, this study aimed to capture older people's bereavement stories and the effects of grief on their physical and mental health. Method: Semi-structured in-depth interviews with 18 bereaved older adults were analysed using thematic and poetic narrative analysis, following a five-step approach of immersion, creation, critical reflection, ethics and engagement. Results: Research poems were used to illustrate three themes of bereavement experiences among older adults: feeling unprepared, accumulation of losses and ripple effects of grief. While half of participants reported that the death of their family member was expected, many felt unprepared despite having experienced multiple bereavements throughout their life. Instead, the accumulation of losses had a compounding effect on their health and well-being. While these ripple effects of grief focussed on emotional and mental health consequences, many also reported physical health effects like the onset of a new condition or the worsening of an existing one. In its most extreme form, grief was connected with a perceived increased mortality risk. Conclusions: By using poetry to draw attention to the intense and often long-lasting effects of grief on older people's health and well-being, this article offers emotional, engaging and immersive insights into their unique bereavement experiences and thereby challenges the notion that grief has an expiry date.